Academic Self-Efficacy and Thesis-Related Anxiety Among Undergraduates: A Comparative Analysis - Adinda, Regina Sekkar; Soetjiningsih, Christiana Hari (Jurnal Bimbingan dan Konseling Terapan, 2024)
This study aimed to examine the relationship between academic self-efficacy and thesis-related anxiety among undergraduate students. A total of 202 participants were involved, and data were collected using Likert scale questionnaires assessing academic self-efficacy and thesis-related anxiety. The results revealed a significant negative correlation between academic self-efficacy and thesis-related anxiety, indicating that higher levels of academic self-efficacy were associated with lower levels of anxiety and vice versa. The majority of participants displayed moderate academic self-efficacy, while most experienced low anxiety levels. Additionally, the duration of thesis work was found to impact anxiety levels and academic self-efficacy, with longer durations correlating with increased anxiety and decreased self-efficacy. These findings highlight the importance of addressing academic self-efficacy to alleviate anxiety during the thesis process. However, it is essential to consider other influencing factors, such as personal resilience and institutional support, and to acknowledge that anxiety levels can be influenced by various external factors not explored in this study.